The revival of military rule in South and Southeast Asia : dangers to the region's democratic future - Kurlantzick, Joshua (Discussion paper (Council on Foreign Relations), 2022)
The rise in coups and other types of military intervention in South and Southeast Asia will set back democracy by years and has been met by a weak and ineffective response from major global and regional powers.